Progressive damage analysis based on vibration signatures : an application to a masonry arch - Ramos, Luís F. (2007)
The paper aims at exploring damage assessment in masonry structures at an early stage by vibration measurements. One arch replicate of historical constructions was built as reference, undamaged, state. Afterwards, progressive damage was induced and sequential modal identification analysis was performed at each damage stage, aiming to find adequate correspondence between dynamic behaviour and internal crack growth.